Design of an automatic hand washing device for elementary school students in Serang for enhanced Covid-19 prevention - Hasanah, Indah Uswatun; Partuti, Tri; Dwiyanti, Yanyan; Kambuna, Bening Hidayah (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
This community service activity aims to educate elementary school students in Serang City, especially at SDN Kewunen, about hand hygiene's importance in preventing COVID-19. The training involved making a simple automatic soap dispenser from used items such as plastic bottles and injections. With a participatory method, students were directly involved, assisted by visual guides in the form of leaflets, posters, and banners. As a result, most students succeeded in making the tools independently at home with the support of their parents and understood the importance of hand hygiene. Monitoring through surveys and teacher testimonials showed a positive response. This program improves students' skills in maintaining cleanliness and fosters environmental awareness through using used goods. Kegiatan pengabdian ini bertujuan mengedukasi siswa SD di Kota Serang, khususnya di SDN Kewunen, tentang pentingnya kebersihan tangan sebagai pencegahan COVID-19. Pelatihan melibatkan pembuatan tempat sabun otomatis sederhana dari barang bekas seperti botol plastik dan suntikan bekas. Dengan metode partisipatif, siswa dilibatkan langsung, dibantu panduan visual berupa leaflet, poster, dan spanduk. Hasilnya, mayoritas siswa berhasil membuat alat secara mandiri di rumah dengan dukungan orang tua dan memahami pentingnya kebersihan tangan. Monitoring melalui survei dan testimoni guru menunjukkan respon positif. Program ini meningkatkan keterampilan siswa dalam menjaga kebersihan dan menumbuhkan kesadaran lingkungan melalui pemanfaatan barang bekas.